PENGARUH SELF CONFIDENCE SISWA TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA SMK NEGERI DI KOTA CIMAHI - Linda Faudziah; Gida Kadarisma (Journal on Education, 2019)
This study aims to conduct an analysis in order to determine the effect of students' self confidence in the mathematical reasoning abilities of vocational students. The method carried out by researchers is a correlational research method based on a quantitative approach, which connects the presence or absence of influence in mathematical reasoning ability with self confidence. Sampling of research conducted is as many as 20 students in one of the State Vocational Schools in Cimahi City. In this case the two influences of cognitive and affective abilities consist of tests and non-tests. The test is done by using mathematical reasoning abilities using three indicators as many as 5 items, while the non test uses a self confidence questionnaire of 20 statement scale. Based on the results that have been obtained that students' self confidence has a positive influence on the ability to think mathematical reasoning of vocational students.